Invasive ductal carcinoma of breast with stromal osteoclast-like giant cells - Sohaila Fatima; Shaymaa Ahmed Sadek (Tropical Journal of Pathology and Microbiology, 2023)
Carcinomas containing multinucleated osteoclast-like giant cells (OGCs) arise in many organs. It is extremely rare, occurring in less than 2% of breast cancer patients. It is associated with ductal, lobular, mucinous, cribriform, papillary, and metaplastic histological subtypes of invasive breast carcinomas. OGCs are thought to be histiocytic in origin, developing in response to breast cancer induced hyper vascular microenvironments. Their significance and role as prognostic marker are not clear. Here we present a female with a mass in left breast which was diagnosed as invasive ductal carcinoma with stromal osteoclast-like giant cells.